Assessing climate-smartness of agronomic practices in oil palm production under changing climate conditions - Lisma Safitri; Marcelo V. Galdos; Iput Pradiko; Alexis Comber; Andrew Challinor (European Journal of Agronomy, 2026)

Deciphering spatial pattern and environmental drivers of deep soil moisture security: insights from integrating spatial non-stationarity in large-scale analysis - Yongping Tong; Yunqiang Wang; Zimin Li; Pingping Zhang; Wei Hu; Jingxiong Zhou; Xiangyu Guo; Hui Sun; Alexis Comber; Ronny Lauerwald (CATENA, 2025)

Geographically weighted accuracy for hard and soft land cover classifications: 5 approaches with coded illustrations - Alexis Comber; Naru Tsutsumida (International Journal of Remote Sensing, 2023)

A spatial analysis of plant phenophase changes and the impact of increases in urban land use - Alexis Comber; Chris Brunsdon (International Journal of Climatology, 2015)
Changes in phenology are indicators of climate change. Urban land use influences local climates through mechanisms such as urban heat island ( UHI ) effects. This research examined the spatio‐temporal variations in first flowering with changes in urban land use in England and Wales. It used standard ordinary least squares ( OLSs ) regressions and geographically weighted regressions ( GWRs ) to analyse changes in phenophase observation date between 1934 and 2007 for three tree species. The OLS models suggested that first flowering was getting earlier: blackthorn by 0.28 days per year, hawthorn by 0.16 days per year and horse chestnut by 0.13 days per year. These rates were found to vary spatially when GWR was used and the greatest rates of change were found to be highly localized. The addition of land use change was found to improve the model fit and suggested that a 10% increase in urban land use was also associated with phenophase advancement of 1.20 days for blackthorn, 0.57 days for hawthorn and 0.90 days for horse chestnut. When the impacts of urban land use changes was analysed using GWR , the associations with phenophase advancement were found to vary spatially, strongest associations were generally more pronounced in the north and especially in the extreme south‐west and the north for all species. The results of this research suggest that the impacts of climate changes and the effects of urban land use changes on phenology vary spatially and that the impacts of urban expansion, such as UHI effects, may not be uniform. These findings suggest the need for spatially explicit analyses to quantify the local impacts and drivers of climate changes and their associated feedbacks.

Managing uncertainty when aggregating from pixels to objects: habitats, context-sensitive mapping and possibility theory - Alexis Comber; Katie Medcalf; Richard Lucas; Peter Bunting; Alan Brown; Daniel Clewley; Johanna Breyer; Steve Keyworth (International Journal of Remote Sensing, 2010)